Análise de cartazes cinematográficos na perspectiva da enunciação - Krahl, Aline (2016)
The purpose of this study is to analyze the semiotic and semantic levels, based on Émile Benveniste’s Enunciative Theory in movie titles in Portuguese, which the original was written in English. The main objective is to compare wether the meaning of the title presented on the poster in Portuguese language mantains the same meaning on the poster originally produced in English. The theoretical setting is based on Émile Benveniste’s Enunciative Theory, based on the books Problems in General Linguistics I (2005 [1966]) and Problems in General Linguistics II (1989 [1974]), along with studies performed by Flores and Teixeira (2005), Flores (2013), Nunes (2012), among others authors mentioned and surveyed during the proceeding of this study. In this setting, we use a corpus composed by three pairs of movie posters. This research is explicative, bibliographical and documental, within a qualitative approach. After selecting the corpus, we performed the analysis of each poster in three steps: 1) the movie synopsis, with a brief description of the plot, in order to help the reader understand the analysis; 2) description of the textual and non-textual elements that appear on the movie poster; and 3) enunciative analysis about the poster, considering the form and meaning that each title have, observing if the meaning changes in Portuguese and English. With this research we can demonstrate that, although the title created in Portuguese has a commercial obje ctive and the intention of being attractive to the audience, there is the concerning in mantaing a similar meaning in both languages, since the object of these titles, the movie, does not change. What changes is the moment of the Enunciation.